Potential anticarcinogenic effect of goat milk-derived bioactive peptides on HCT-116 human colorectal carcinoma cell line - AKBAY, TUĞBA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Novel food-derived anti cancerogenic bioactive peptides were characterized by goat milk pepsin hydrolysate. Pepsin treated casein fraction of goat milk caused an apoptotic cell death on the HCT116 cell lines. These bioactive peptides are encrypted in the protein structure in the inactive form and can become active during gastrointestinal digestion in the body. In this study, the possible therapeutic effect of goat milk-based bioactive peptides on human colorectal cancer cell lines was investigated. Goat milk-derived bioactive peptides were extracted from the casein and whey protein fractions using trypsin, pepsin, and papain enzymes. The bioactive peptides were characterized by the liquid chromatography quadrupole time of flight mass spectrometry. Both enzyme-treated casein and whey fractions were incubated with the HCT116 cell lines, and then the cell cytotoxicity was evaluated using MTT assay. The type of cell death was analyzed by flow cytometry using Annexin V and propidium iodide. Among all applications, the pepsin-treated casein fraction was the highest potential peptides that cause 80.92% apoptotic cell death. In conclusion, pepsin treated casein fraction exhibited antiproliferative activity against HCT116 cells. The bioactive peptides of this fraction can be considered as a potential source for the development of new anti cancerogenic agents.
Keywords: Goat milk; Bioactive peptides; HCT 116 cell lines; MTT assay; Flow cytometry; Liquid chromatography quadrupole time of flight mass spectrometry; DAIRY-PRODUCTS; PROTEINS; IDENTIFICATION; CANCER; APOPTOSIS; ENZYME